DESKRIPSI KEGIATAN BUDIDAYA TOGA BERBASIS URBAN FARMING SERTA ASPEK KENDALA YANG DIHADAPI: SUATU KASUS TOGA KUNYIT DI KELURAHAN RANCABOLANG, KECAMATAN GEDEBAGE, KOTA BANDUNG - Elly Rasmikayati; Anton Eisa Putra; Bobby Rachmat Saefudin (Universitas Galuh Ciamis, 2021)
Rancabolang Village, Gedebage Subdistrict, Bandung City is one of the sub-districts which in several RWs has carried out the cultivation of TOGA plants based on urban farming. However, in reality, the program has not run optimally because it has not been able to absorb all members to be able to play an active role. This study aims to determine the description of the implementation of the TOGA plant cultivation activity based on urban farming and the obstacles experienced by the community during its implementation. The data and information obtained is analyzed using descriptive statistics. The results showed that TOGA cultivation activities in Rancabolang Village have not been able to get to the production stage to be used economically. This is because most of the harvest is only used by PKK group members and harvesting activities are not carried out routinely when it reaches harvest time. There are 4 aspects of the constraints discussed in this study. In terms of the constraints on TOGA cultivation, limited land is the main obstacle and another obstacle is the need for seeds. In the aspect of harvest constraints, unscheduled and irregular harvesting processes are the main obstacles. On the marketing aspect, the small amount of production is the main obstacle. In the organizational aspect, member participation is the main obstacle and another obstacle is the routine meeting activities to discuss TOGA cultivation.